HETEROGENEOUS TEXTURES OF SOWN AREAS ANALYSIS, BASED ON MIXTURE DIVISION ESTIMATION - Курочкин, В. М.; Приставка, Ф. О. (Science-based technologies, 2015)
The special case in digital aerial photography of agricultural areas processing and analysis considered, when a certain area of the field identified as a complex structure, consisting of two unimodal intensity distributions. Introduced a concept of productivity function, based in the reproducing distribution mixtures procedure and the percentage of “green” component. Based on the heterogeneous texture analysis and heterogeneous distribution mixture estimation a visual representation of the yield of the agricultural area built. An algorithm for constructing such a representation based on method of moments evaluation of two normal distributions mixtures and use of two-dimensional splines, based on second order B-splines for separated sectors of the area to build a general map of the distribution of productivity presented. The results of the research with image samples of built software output and the findings of the study, prospects for further work shown.